Safety of Nanoclay/Spring Water Hydrogels: Assessment and Mobility of Hazardous Elements - Fátima García-Villén; Rita Sánchez-Espejo; Ana Borrego-Sánchez; Pilar Cerezo; Luana Perioli; César Viseras (MDPI AG, 2020)
The presence of impurities in medicinal products have to be controlled within safety limits from a pharmaceutical quality perspective. This matter is of special significance for those countries and regions where the directives, guidelines, or legislations, which prescribe the rules for the application of some products is quite selective or incomplete. Clay-based hydrogels are quite an example of this matter since they are topically administered, but, in some regions, they are not subjected to well-defined legal regulations. Since hydrogels establish an intimate contact with the skin, hazardous elements present in the ingredients could potentially be bioavailable and compromise their safety. The elemental composition and mobility of elements present in two hydrogels have been assessed. Sepiolite, palygorskite, and natural spring water were used as ingredients. The release of a particular element mainly depends on its position in the structure of the hydrogels, not only on its concentration in each ingredient. As a general trend, elements' mobility reduced with time. Among the most dangerous elements, whose presence in cosmetics is strictly forbidden by European legal regulations, As and Cd were mobile, although in very low amounts (0.1 and 0.2 μg/100 g of hydrogel, respectively). That is, assuming 100% bioavailability, the studied hydrogels would be completely safe at normal doses. Although there is no sufficient evidence to confirm that their presence is detrimental to hydrogels safety, legally speaking, their mobility could hinder the authorization of these hydrogels as medicines or cosmetics. In conclusion, the present study demonstrates that hydrogels prepared with sepiolite, palygorskite, and Alicún spring water could be topically applied without major intoxication risks.